2020
DOI: 10.3904/kjim.2020.022
|View full text |Cite
|
Sign up to set email alerts
|

Distinct functions of eosinophils in severe asthma with type 2 phenotype: clinical implications

Abstract: Asthma is commonly recognized as a heterogeneous condition with a complex pathophysiology. With advances in the development of multiple medications for patients with asthma, most asthma symptoms are well managed. Nevertheless, 5% to 10% of adult asthmatic patients (called severe asthma) are in uncontrolled or partially controlled status despite intensive treatment. Especially, severe eosinophilic asthma is one of the severe asthma phenotypes characterized by eosinophilia in sputum/blood driven by type 2 immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 102 publications
0
29
0
Order By: Relevance
“…It is characterized by excessive inflammation of bronchi and obstruction of the airflow due to increased immune responses, resulting in varying respiratory symptoms, mainly difficulty in breathing, wheezing, coughing, and tightness in the chest [ 3 , 8 , 9 ]. Based on its main characteristics, asthma has been divided into molecular pathways/clinical presentations or atopic/non-atopic asthma and more recently, into eosinophilic or non-eosinophilic phenotypes based on biological mechanisms [ 10 ]. Proinflammatory cytokines are key players in the development and progression of asthma, and they induce elevated immune responses, resulting in characteristic asthmatic responses such as eosinophilia, airway hyperresponsiveness (AHR), airway remodeling, and mucus production [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by excessive inflammation of bronchi and obstruction of the airflow due to increased immune responses, resulting in varying respiratory symptoms, mainly difficulty in breathing, wheezing, coughing, and tightness in the chest [ 3 , 8 , 9 ]. Based on its main characteristics, asthma has been divided into molecular pathways/clinical presentations or atopic/non-atopic asthma and more recently, into eosinophilic or non-eosinophilic phenotypes based on biological mechanisms [ 10 ]. Proinflammatory cytokines are key players in the development and progression of asthma, and they induce elevated immune responses, resulting in characteristic asthmatic responses such as eosinophilia, airway hyperresponsiveness (AHR), airway remodeling, and mucus production [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eosinophilia in peripheral blood and upper/lower airway mucosa are commonly found in AERD patients [ 3 ]. Although both mast cells and eosinophils are critical for inducing airway inflammation in the pathogenesis of AERD, emerging evidence supports an important role of eosinophils in its pathogenesis [ 4 , 5 ]. AERD patients have shown that significantly elevated levels of eosinophil-derived granule proteins, such as eosinophil cationic protein (ECP) and eosinophil-derived neurotoxin (EDN), compared to aspirin-tolerant asthma (ATA) patients [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggested that during virus infection and lung injury, circulating EOS are recruited to the lung tissue to mediate the antiviral response, and this might lead to the decreased amount of EOS in the circulatory system ( 15 , 16 ). Other studies also showed that EOS were recruited to the lungs during the development of asthma ( 17 ). On the other hand, viral infection caused disturbance of the homeostasis of bone marrow, which might further lead to aberrant hematopoiesis ( 18 ) and abnormal production of EOS ( 19 ).…”
Section: Discussionmentioning
confidence: 92%